Castro's Cuba and the U.S. Helms-Burton Act : an interpretation of the GATT security exemption. - KUILWIJK, Kees Jan (1997)
Argues that the Helms-Burton Act violates various principles and provisions of WTO law and cannot be justified under Article XXI of the GATT or Article XIVbis of GATS.